Pembelajaran Pancasila Anak Usia Dini Melalui Media Visual Di Taman Pendidikan Al-Qur’an Di Kota Makassar - Rara Khaira; Revaldo Wijaya; Hijriani Hijriani; Amelia Jamaluddin; Nadhyra Safitri Khairunnisa; Salsabila Alifya Hasan; Aan Aan (Contemporary Education Review, 2025)
This study aims to examine the effectiveness of using visual media in teaching basic national values to early childhood students. The research was conducted at a Quranic Education Park in Makassar City, involving 23 children aged between four and twelve years. The method employed was a qualitative approach with a participatory observation design, where the researcher directly observed the children's engagement and understanding of the material presented. Data collection techniques included direct observation, informal interviews, and question-and-answer sessions tailored to the children's developmental stage. The learning media was developed in the form of a visual presentation containing cartoon illustrations and simple explanations relevant to the children's everyday life. The data were analyzed descriptively and qualitatively by grouping findings based on indicators of understanding the values of Pancasila. The results showed that before the intervention, the children were only able to memorize the content of Pancasila without understanding its meaning. After the visual media-based learning, the children demonstrated a significant improvement in their understanding of the meaning of each principle and were able to relate it to concrete behaviors in daily life, such as sharing, helping friends, and maintaining environmental cleanliness. Visual media proved to play an important role in attracting attention, stimulating interest in learning, clarifying abstract concepts, and assisting children who struggled to understand verbal explanations. Therefore, the use of visual media is an appropriate approach in supporting the internalization of basic national values in a fun and meaningful way for early childhood.